Tuning the Legacy Survey of Space and Time (LSST) Observing Strategy for Solar System Science - Schwamb, Megan E.; Jones, R. Lynne; Yoachim, Peter; Volk, Kathryn; Dorsey, Rosemary C.; Opitom, Cyrielle; Greenstreet, Sarah; Lister, Tim; Snodgrass, Colin; Bolin, Bryce T.; Inno, Laura; Bannister, Michele T.; et al. (The Astrophysical journal. Supplement series, 2023)
The Vera C. Rubin Observatory is expected to start the Legacy Survey of Space and Time (LSST) in early to mid-2025. This multiband wide-field synoptic survey will transform our view of the solar system, with the discovery and monitoring of over five million small bodies. The final survey strategy chosen for LSST has direct implications on the discoverability and characterization of solar system minor planets and passing interstellar objects. Creating an inventory of the solar system is one of the four main LSST science drivers. The LSST observing cadence is a complex optimization problem that must balance the priorities and needs of all the key LSST science areas. To design the best LSST survey strategy, a series of operation simulations using the Rubin Observatory scheduler have been generated to explore the various options for tuning observing parameters and prioritizations. We explore the impact of the various simulated LSST observing strategies on studying the solar system's small body reservoirs. We examine what are the best observing scenarios and review what are the important considerations for maximizing LSST solar system science. In general, most of the LSST cadence simulations produce ±5% or less variations in our chosen key metrics, but a subset of the simulations significantly hinder science returns with much larger losses in the discovery and light-curve metrics.